Pengaruh Tiktok Shop terhadap Pedagang Pasar Tradisional di Pasar Tanjung dan Ambulu Kabupaten Jember - Nadia Ulva Febrianti; Shalsa Aina Widi Zahrafani; Wafiatul Afifah (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
A traditional market is a place built and managed by the government or private sector in the form of stalls, booths or shops. Without realizing it, the market is also a place for social interaction, because the market is a place where bargaining takes place between sellers and buyers. However, along with the development of technology and science, the existence of the tiktok shop application has made activities in the market increasingly quiet, the income of market traders has decreased, and customers have switched to online shops because they are looking for goods at more reasonable prices with better quality. This research uses the lens of conflict theory presented by Ralf Dahrendorf. According to Dahrendorf, conflict theory is that every society at every point is subject to processes of change. The purpose of this study is to determine the impact of the presence and absence of tiktok shop for traditional market traders. This type of research uses qualitative research with a phenomenological approach. The results of this study show that there is indeed a gap between market traders due to the impact of the covid phenomenon and the emergence of the tiktok shop, the impact is still felt even though the tiktok shop has been closed, such as the impact of decreased income for market traders. Market traders in Ambulu and Tanjung hope that market conditions will soon recover to what they were before the tiktok shop.